Association between Maternal Mental Health after Early Marriage and Adolescent Mental Disorders in Indonesia - Cahyono, Budi; Kartiningrum, Eka Diah; Alamudi, Mohammad Yusuf (Universitas Syiah Kuala, 2025)
Background: Early marriage remains a persistent social phenomenon with profound implications for maternal mental health and the psychological development of children. This study aims to examine the association between maternal mental health following early marriage and the occurrence of mental disorders among adolescents in Malang Regency, Indonesia.Methods: A quantitative cross-sectional design was employed with a total of 205 respondents selected using a quota-based multistage sampling technique. Data were collected through standardized questionnaires measuring maternal mental health and adolescent mental disorders using the Symptom Checklist-90 (SCL-90). Statistical analyses included ordinal logistic regression and Chi-Square tests (Pearson and Likelihood Ratio) to assess associations and predictive effects.Results: Findings demonstrated a significant association between maternal mental health after early marriage and the prevalence of mental disorders among adolescents. Ordinal logistic regression revealed that maternal mental health status significantly influenced adolescent mental health outcomes. The model showed good fit (Goodness-of-Fit Pearson = 10.164, p = 0.602; Deviance = 11.249, p = 0.508) with a moderate to strong effect size (Nagelkerke Pseudo R = 0.521). Parameter estimates indicated a positive direction of influence: higher levels of maternal mental health problems were associated with a greater likelihood of adolescent mental disorders.Conclusion: Maternal mental health following early marriage has a substantial impact on adolescent psychological well-being. The study highlights the urgent need for comprehensive public health policies to prevent early marriage and to provide accessible mental health support services for mothers and adolescents in Indonesia.